Development of the banking system on agricultural economic growth During the period (2010_1990) - Sabah Elsaadi (Journal of Pure & Applied Sciences, 2019)
The research discussed the impact of the evolution of the banking system on the agricultural economic growth during the period (1990-2010). The agricultural sector is considered one of the major economic sectors in terms of its contribution to food security, growth and poverty reduction. Determine the role of the banking sector in supporting agricultural economic development. The purpose of this study was to analyze and measure the impact of the volume of credit granted by the banking sector on the agricultural economy and the extent of its contribution to the agricultural output of Libya and to know the role of the Central Bank of Libya in regulating and controlling the work of banks. The study was based on a model to prove the study hypothesis, And a standard model using the Eviews program was used to test the study model. The results of the descriptive and standard analysis showed that the independent variables (total loans and agricultural employment) have a positive effect on agricultural GDP in the short and long term on GDP, and that the statistical model is statistically significant. The study recommended the necessity of building a national plan for agricultural economic development and paying attention to medium and long-term loans at an attractive price to achieve sustainable agricultural development, promote political and security stability, and support agricultural employment.